IMPLEMENTATION OF ULTRASONIC SENSOR HCSR04 BASED ON Arduino UNO AS A SOCIAL DISTANCE TOOL IN THE NEW NORMAL ERA - Adam Robby Arifin; Lela Nurpulaela; Reni Rahmadewi (Power Elektronik : Jurnal Orang Elektro, 2022)
Abstract  This study aims to design and construct an Arduino- based HC-Sr04 Ultrasonic sensor in reducing the spread of Covid- 19 in this new normal era. The ultrasonic sensor will be used as a device that can detect the presence of object in front of it by utilizing ultrasonic waves emitted by the transmitter on the sensor. Through these advantages, the device is used as a warning medium to keep a distance according to the Covid-19 prevention protocol in the new normal era. As is often campaigned, social distancing is one of the efforts that greatly affects the spread of the corona virus, so that through the design and implementation of this system, it is hoped that this can be achieved. In the research process, an ultrasonic sensor is used to measure distance, then the data will be sent to Arduino as the microcontroller or brain of this system. Simply put, when the object approaches the sensor at a predetermined distance limit, Arduino will process the data and then immediately give a command to activate the buzzer. The results of the research carried out are a product of automatic distance limiting technology using the HC-Sr04 ultrasonic sensor based on Arduino Uno which of course can provide benefits, especially in a pandemic situation like today.Keywords: Ultrasonic HC Sr 04, Arduino, Covid-19, New Normal